New Determinants of Political Socialization in the Internet Age - Pawełczyk, Piotr; Jakubowski, Jakub (Wydawnictwo Nakowe WNPiD UAM w Poznaniu, 2019)
The media appears to play an increasingly significant role in the process of political socialization. This is the outcome of the large amount of time people spend every day in front of their screens and other sources of information on the one hand, and from the growing ‘intimacy’ of their relations with their devices. A majority of Poles (ca. 64% in 2017 in the 15+ age group) have smartphones, and thus the possibility of being online at practically every moment. This proportion can be assumed to be even higher among schoolchildren. This precipitates a question of the extent to which access to the web influences the process of political socialization, and what impact it has on the processes of social adjustment. This article attempts to compare and review theoretical tenets of the concept of political socialization. The validity of some assumptions made in the pre-internet area is questioned in the face of the contemporary reality of the world operating in permanently-logged-in mode. A handful of recommendations are also put forward for a more socially useful application of the media in the adjustment of the individual (in particular young people) to living in the circumstances of media democracy.

W procesie socjalizacji politycznej media wydają się odgrywać coraz istotniejszą rolę. Wynika to nie tylko z dużej ilości czasu spędzanego każdego dnia przed ekranami i innymi nośnikami informacji, ale i coraz większej „intymności” w relacjach z urządzeniami – większość Polaków (ok. 64% w 2017 r. w grupie 15+) posiada smartfon, który daje możliwości bycia online niemalże w każdym momencie życia. Należy założyć, iż w grupie młodzieży szkolnej, odsetek ten jest większy. Skłania to do zadania pytania: na ile dostęp do sieci wpływa na proces socjalizacji politycznej i jakie są jego skutki w obszarze procesów społecznego dostosowania? Celem artykułu jest ich zestawienie i próba zrewidowania założeń teoretycznych dotyczących pojęcia socjalizacji politycznej. Poddajemy w wątpliwość aktualność pewnych założeń ery przedinternetowej w stosunku do współczesnych realiów świata funkcjonującego w trybie permanent-logged-in. Wysuwamy też propozycję kilku rekomendacji mogących stanowić podstawę do bardziej użytecznego społecznie wykorzystania mediów w obszarze dostosowania się (w szczególności młodej) jednostki do życia w warunkach demokracji medialnej.
Nowe determinanty socjalizacji politycznej w dobie Internetu
Keywords: political socialization; social media; media education; the internet; socjalizacja polityczna; social media; edukacja medialna; Internet